Network Security Scheme for Discrete-Time T-S Fuzzy Nonlinear Active Suspension Systems Based on Multiswitching Control Mechanism - Shen, Jiaming; Liu, Yang; Chadli, Mohammed (IEEE transactions on fuzzy systems, 2025)
This article investigates the cybersecurity problem of active suspension systems (ASSs) subject to random denial-of-service (DoS) attacks. Consider the nonlinearity and uncertainty of ASSs, the Takagi-Sugeno (T-S) fuzzy theory is applied to address these issues. In order to model various potential operating behaviors of the system, a high-order multiswitching-mode (HOMSM) T-S fuzzy control scheme is constructed, in which a series of free-weighted matrix sets are developed for different switching modes, such that the conservatism of controller design is reduced to a certain extent. By designing the HOMSM control method, a certain level of resistance to randomly activated DoS attacks can be achieved. With the help of homogeneous polynomial technology, several time-varying balance matrices are constructed for extracting the properties of different switching modes. Then, the exponential stability conditions of ASSs under DoS attacks can be derived, and the H_{∞ } performance criterion is guaranteed. Finally, the theoretical results are validated by the hardware-in-the-loop experiments.